2023
DOI: 10.3390/nu15061457
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Globularia alypum Explored Ex Vivo In Vitro on Human Colon Biopsies from Ulcerative Colitis Patients

Abstract: The existing literature indicates that Globularia alypum L. (GA) influences inflammation and oxidative stress modulation in rats and in vitro. The present study aims to investigate the effects of this plant in patients with ulcerative colitis (UC) and normal controls. In our experiments, we pretreated colon biopsies from 46 UC patients and normal controls with GA leaves aqueous extract (GAAE) used at two concentrations (50 and 100 µg/mL) for 3 h, followed by Lipopolysaccharides (from Escherichia coli) stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…However, administration of yohimbine regenerates antioxidant enzyme levels. GAAE also significantly increased SOD and GPx levels in a dose-dependent manner (400 mg/kg) [13]. The results of a second Algerian investigation demonstrated that G. alypum methanolic and aqueous extracts, which were obtained in June 2010 from Sétif in Eastern Algeria, could chelate ferrous ions in a concentration-dependent way.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, administration of yohimbine regenerates antioxidant enzyme levels. GAAE also significantly increased SOD and GPx levels in a dose-dependent manner (400 mg/kg) [13]. The results of a second Algerian investigation demonstrated that G. alypum methanolic and aqueous extracts, which were obtained in June 2010 from Sétif in Eastern Algeria, could chelate ferrous ions in a concentration-dependent way.…”
Section: Discussionmentioning
confidence: 86%
“…These elements may have a direct impact on the composition of chemical components. Given their high phenolic component content, our obtained extracts will probably show a range of biological activity [13]. For instance, Calvin et al reveled that nepetin isolated from Eupatorium arnottianum (EA) was investigated in the TPA mouse ear edema and was found to be active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation